Prevalence of Extended Spectrum Beta-Lactamases Producing Enterobacteriaceae in Sheep and Goats from Selected Markets in Ibadan, Oyo-State, Nigeria (2023)
Antìmicrobial misuse, unhygienic husbandry practices, dose interaction between humans and animai as obtained in livestock market facilitate thè emergence, dissemination and transmission of resistant Enterobacteriaceae. These organisms are responsible for various intestinal and extra-intestinal infections in human and animals. According to this report, thè prevalence of Extended Spectrum Beta-Lactamase (ESBL)-producing Enterobacteriaceae in sheep and goats from selected markets in Ibadan. Three hundred and four (304) samples were collected for a cross-sectional survey among thè sheep and goat markets in Ibadan. From thè same sheep and goats, 152 milk samples and 152 faeces samples were collected. In order to identify any antibiotic-resistant Enterobacteriaceae, these samples underwent bacteriological analysis. On MacConkey agar plates with 1 mg/L cefotaxime added, all samples were cultivated. Utilizing a biochemical test kit (Oxoid Microbact GNB 24E®), thè isolates were identified. ESBL products were evaluated utilizing a doublé disc diffusion test with discs impregnated with cefpodoxime and cefpodoxime-clavulanic acid. By using thè disc diffusion approach, antibiotic resistance was identified. Data was analysed using descriptive statistics. Eighty-eight ampicillin resistant Enterobacteriaceae strains were isolated from 304 samples collected and 23 (26.1%) of thè isolates were cefotaxime- resistant Enterobacteriaceae isolates. Only 9(10.2%) were confirmed phenotypic ESBL-producers and they were all from faeces. AH ESBL -producing Enterobacteriaceae were E. coli strain and showed 100% resistance to tetracycline and ceftazidime, 77.8% resistance to amoxicillin and sulphamethoxazole but susceptible to gentamycin and ciprofioxacin in this investigation. The ESBL-producing E. coli isolates showed different antibiotic resistance pattems. In this study, 100% of ESBL-producing E. coli were multidrug- resistant, showing resistance to at least three separate classes of antibiotics. Public awareness of thè significance of stringent hygiene in animai husbandry needs to be raised in light of thè possible threat that thè existence of multidrug resistant ESBL-producing E. coli in small ruminants poses to public health